122 Endothelial loss as a cause of impaired myocardial perfusion reserve in severe aortic stenosis. (May 2019) - Chan, Kenneth; Raman, Betty; Westaby, Joseph; Dass, Sairia; Petrou, Mairo; Sayeed, Rana; Ashrafian, Houman; Myerson, Saul; Karamitsos, Theodoros; Sheppard, Mary; Neubauer, Stefan; Mahmod, Masliza
Abstract : Introduction: Impaired myocardial perfusion reserve occurs in pressure overload hypertrophy such as in severe aortic stenosis (AS) despite unobstructed epicardial coronaries. However the pathological mechanisms underlying this are poorly understood. We sought to assess myocardial perfusion reserve in severe AS by stress perfusion cardiovascular magnetic resonance (CMR), and examine the findings in relation to the histological evidence of vascular changes in the myocardium. Methods: Fourteen patients with severe AS and unobstructed epicardial coronaries underwent adenosine stress perfusion CMR before and 6 months after surgical aortic valve replacement (AVR). Myocardial biopsies were obtained during AVR and stained using CD31+ for endothelium, smooth muscle actin (SMA) for smooth muscle, and picrosirius red for fibrosis. Nine age- and sex- matched post-mortem myocardial samples served as histological controls. Results: When compared to controls, the myocardium of patients with severe AS had reduced vessel density, total quantity of SMA+ve and CD31+ve, in addition to the expected increase in fibrosis. (figure 1 ) There was absence of CD31+ve endothelium in SMA+ve arterioles, indicating endothelial loss. Importantly, patients with an aortic valve area (AVA) ≤0.8cm 2 had greater endothelial loss compared to those with an AVA >0.8 and ≤1.0cm 2 (1.34±0.44% vs 2.84±1.03%, p=0.006), and endothelial loss also correlated with myocardial perfusion reserve index (MPRI), r=0.66, p=0.019. MPRI improved significantly post AVR (from 0.95±0.17 to 1.50±0.43, p=0.018). Conclusion: In severe AS, there is microvascular rarefaction and loss of endothelium, which is more pronounced in patients with the most severe aortic valve narrowing. This appears to be an underlying mechanism for reduced myocardial perfusion reserve, which may be reversible post AVR. Conflict of Interest: None